Methionine Requirement for Juvenile White Seabass, Atractoscion nobilis, Using Nonlinear Models. Issue 5 (2nd March 2017) - Salze, Guillaume P.; Davis, Donald A.; Jirsa, Dave O.; Drawbridge, Mark A.
Abstract: Two trials were conducted to estimate the methionine (Met) requirement of juvenile white seabass, Atractoscion nobilis . Diets were formulated to contain 40% crude protein, 10% lipids, and 0.51% cysteine. Graded levels ofdl ‐Met were added to create seven diets with dietary Met levels ranging from 0.72 to 0.98%, and nine diets ranging from 0.64 to 1.28% Met in Trials A and B, respectively. Thermal‐unit growth coefficient was fitted to dietary Met levels to estimate the Met requirement using the saturation kinetic model (SKM), the quadratic model (QM), or the broken quadratic model (BQM). The 95% confidence interval (CI) was estimated through the iterative fitting process for the BQM and using a bootstrapping approach for the QM and SKM. In Trial A, the three models estimated the requirement between 0.88 and 1.08%, with wide CI. In Trial B, precisions of the requirement estimates by the SKM and BQM were significantly improved compared with Trial A, though BQM evidently overestimated the requirement. SKM provided the best fit; hence, we conclude that the Met requirement for juvenile white seabass is 0.88% (95% CI: 0.80–1.08%) in the presence of 0.51% cysteine. This estimate provides valuable basis for the formulation of practical diets for juvenile white seabass.